2005
DOI: 10.1007/s00520-005-0826-3
|View full text |Cite
|
Sign up to set email alerts
|

Treating sialorrhea with transdermal scopolamine. Exploiting a side effect to treat an uncommon symptom in cancer patients

Abstract: Anticholinergic drugs are classified as secondary options in the treatment of sialorrhea of patients with Parkinson's disease or cerebral palsy, owing to the relevant side effects occurring during prolonged treatments. However, they could be useful in cancer patients with bowel subocclusion, as the reduction of gastrointestinal secretions and intestinal motility (frequent side effects of anticholinergic drugs) could be effective in controlling nausea, vomiting, and abdominal pain. Moreover, the transdermal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…It is possible that the application of the circular patch in this region may have a direct effect on the parotid tissue, thus causing a reduction in salivary secretion. The use of transdermal scopolamine to achieve an antisialogogue action has already been described in the management of drooling in patients with neurological disease [12, 13]. Our experience suggests that the use of transdermal scopolamine as antisialogogue can be a conservative, cost effective, and safe strategy for the treatment of posttraumatic parotid fistulas.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…It is possible that the application of the circular patch in this region may have a direct effect on the parotid tissue, thus causing a reduction in salivary secretion. The use of transdermal scopolamine to achieve an antisialogogue action has already been described in the management of drooling in patients with neurological disease [12, 13]. Our experience suggests that the use of transdermal scopolamine as antisialogogue can be a conservative, cost effective, and safe strategy for the treatment of posttraumatic parotid fistulas.…”
Section: Discussionmentioning
confidence: 73%
“…Transcop, developed for the prevention of motion sickness, is a transdermal therapeutic system for controlled delivery for scopolamine. Scopolamine is an antimuscarinic agent that has a powerful action on salivary glands and can reduce the volume of salivary secretion in human beings [12]. The availability of scopolamine in a transdermal delivery system provides an alternative method in the administration of antisialogogues and avoids collateral effects [12, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One case report described reduced salivation within days of scopolamine patch application in an ambulatory patient with advanced peritoneal cancer. 21 Twice-daily topical application of 1% atropine eye drops reduced the severity of drooling in seven patients, six of whom had Parkinson's disease and one who was diagnosed with progressive supranuclear palsy. 16 One patient withdrew from the study because of delirium, which the authors reported was confounded by a urinary tract infection.…”
Section: Studies In Nonhospice Patientsmentioning
confidence: 99%
“…In some chronically critically ill patients with excessive secretions due to multiple-drug-resistant healthcare associated pneumonias or end stage cardiac disease, more frequent changes may be needed. In some instances, additional measures to reduce secretions are worth attempting, such as scopolamine patches 64 or parotid gland injection with botulinum toxin. 65 Once patients start to tolerate SBTs, a one way speaking valve 66 can be used to allow phonation over the vocal cords and also enhance swallowing by augmenting subglottic pressure.…”
Section: Tracheostomy Tube Management During Pmvmentioning
confidence: 99%